Tailored exercise with telehealth monitoring improves adherence and global health in kidney transplant recipients - Vecchiato, Marco; Duregon, Federica; Zanardo, Emanuele; Baioccato, Veronica; Quinto, Giulia; Livio, Alberto; Mazzucato, Barbara; Sarri, Chiara; Bellis, Lia; Carella, Claudia; Cardillo, Massimo; Neunhaeuserer, Daniel; et al. (Frontiers in Sports and Active Living, 2024)
Introduction Tailored exercise prescription is a crucial intervention for kidney transplant recipients (KTRs). This longitudinal study investigates the impact on long-term effectiveness of exercise prescriptions over one year follow-up, implementing telehealth tools for exercise administration and adherence monitoring. Materials and methods KTRs were evaluated with clinical assessments including body composition, blood and urinary parameters, physical performance and quality of life at baseline (T0), after six (T6) and twelve (T12) months. The adherence to prescribed exercise training was monitored via video call interviews until T6 when the sample was divided into a group monitored via wearables (WG) and a group continuing video calls (VG) until T12. Results Twenty-six KTRs completed the study. No changes in body composition and kidney function were reported. KTRs showed an improvement in lipid profile, systolic blood pressure, cardiorespiratory fitness and quality of life. WG showed no clinical differences compared to VG except for reported higher quality of life. Discussion A good adherence to the exercise prescription was obtained with both monitoring methods (232 vs 253 min/week). This study reinforces the inclusion exercise training for KTRs to enhance physical fitness and reduce cardiovascular risk factors. These results emphasize the role of telehealth monitoring methods as motivators for adherence to long-term exercise prescriptions.